Modulation of host immune defenses by Aeromonas and Yersinia species: convergence on toxins secreted by various secretion systems - Rosenzweig, Jason A.; Chopra, Ashok K. (Frontiers in Cellular and Infection Microbiology, 2013)
Like other pathogenic bacteria, Yersinia and Aeromonas species have been continuously co-evolving with their respective hosts. Although the former is a bonafide human pathogen, the latter has gained notararity as an emerging disease-causing agent. In response to immune cell challenges, bacterial pathogens have developed diverse mechanism(s) enabling their survival, and, at times, dominance over various host immune defense systems. The bacterial type three secretion system (T3SS) is evolutionarily derived from flagellar subunits and serves as a vehicle by which microbes can directly inject/translocate anti-host factors/effector proteins into targeted host immune cells. A large number of Gram-negative bacterial pathogens possess a T3SS empowering them to disrupt host cell signaling, actin cytoskeleton re-arrangements, and even to induce host-cell apoptotic and pyroptotic pathways. All pathogenic yersiniae and most Aeromonas species possess a T3SS, but they also possess T2- and T6-secreted toxins/effector proteins. This review will focus on the mechanisms by which the T3SS effectors Yersinia outer membrane protein J (YopJ) and an Aeromonas hydrophila AexU protein, isolated from the diarrheal isolate SSU, mollify host immune system defenses. Additionally, the mechanisms that are associated with host cell apoptosis/pyroptosis by Aeromonas T2SS secreted Act, a cytotoxic enterotoxin, and Hemolysin co-regulated protein (Hcp), an A. hydrophila T6SS effector, will also be discussed.